DEFISIT MODAL SOSIAL DAN KORUPSI DANA DESA: MERITOKRASI CALON KEPALA DESA - Sasongko, Ahmad Bagus; Sulhin, Iqrak (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2022)
The problem of deficit social capital within the village community has given rise to a mode of corruption related to the village. One vulnerable contribution is in the Village Head Election. This is based on the role of the community in their daily activities, which are often at stake to find village leaders to implement democracy in the village. This study discusses the importance of the role of the village community in determining the village head by looking at the village head candidates through their abilities, achievements, and integrity because this will determine the direction of a village to surrender the head of government affairs in the village so that the fulfillment of the rights and obligations of the village community can be fulfilled by using qualitative methods and case studies related to village heads who are suspects in corruption cases, as well as comparative analysis with villages that have received awards as anti-corruption villages. The research results show that strengthening social capital is the foundation for implementing meritocracy. The meritocracy built in the community is based on Leadership, service to the community, managing good village governance, strengthening supervision through local wisdom, and participation in society. So, the evaluation of village head candidates must apply a meritocracy system to prevent corruption at the village level. The community must see that village head election are a means to build village change in a better direction.